2005
DOI: 10.1097/00008469-200508000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Use of intensified early cancer detection in high-risk patients with familial breast and ovarian cancer

Abstract: A prospective follow-up study was carried out to evaluate the influence of risk and genetic counselling on use of early cancer detection. Five hundred and fifty-six subjects who fulfilled inclusion criteria for a genetic analysis of the BRCA1/2 genes (the high-risk group A) and 205 who did not fulfil the inclusion criteria (the lower risk group B) attended primary consultation in the interdisciplinary cancer genetic clinic. Information about participation in the early cancer detection programme was documented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Two study centers screened for both breast and ovarian cancer [127][128][129][130][131] (Table 4). From the Stockholm center (BOC#1) which included 160 high-risk families, the decreasing age of cancer onset with successive generations was considered to be important for choosing surveillance modalities [127].…”
Section: Breast Cancer Edp Among Jewish Womenmentioning
confidence: 99%
“…Two study centers screened for both breast and ovarian cancer [127][128][129][130][131] (Table 4). From the Stockholm center (BOC#1) which included 160 high-risk families, the decreasing age of cancer onset with successive generations was considered to be important for choosing surveillance modalities [127].…”
Section: Breast Cancer Edp Among Jewish Womenmentioning
confidence: 99%
“…Notwithstanding the high frequency of surveillance, these authors found it feasible to motivate at-risk women to participate. despite the problems surrounding false positive findings, Mri was found to be acceptable by these women (84,85). This latter conclusion was shared by authors from the dutch Multicenter study (#1) (38).…”
Section: Benefits Of Imaging Surveillance For Women At High Breast Camentioning
confidence: 69%
“…The investigators from the dusseldorf Center (#13) (84,85) stated that intensified early cancer detection programs for women at risk provide a less invasive option than chemoprevention or prophylactic surgery. Notwithstanding the high frequency of surveillance, these authors found it feasible to motivate at-risk women to participate.…”
Section: Benefits Of Imaging Surveillance For Women At High Breast Camentioning
confidence: 99%
“…For women at elevated ovarian cancer risk, due to heredity, ionizing radiation exposure, or other risk factors, FPT-MRS could also be suitable for surveillance. Aligned with this perspective is the view of women at high ovarian cancer risk [36,67], as well as of women from the general population [68], who have clearly expressed an interest and preference for screening surveillance strategies vis-à-vis ovarian cancer. Most essentially, the survival for women afflicted with ovarian cancer would be markedly improved with early detection of this malignancy.…”
Section: Discussionmentioning
confidence: 99%